The effect of holes in long-lasting insecticidal nets on malaria in Malawi: results from a case–control study - Anna A. Minta; Keren Z. Landman; Dyson A. Mwandama; Monica P. Shah; Jodi L. Vanden Eng; James F. Sutcliffe; Joseph Chisaka; Kim A. Lindblade; Don P. Mathanga; Laura C. Steinhardt (Malaria Journal, 2017)
Abstract Background Long-lasting insecticidal nets (LLINs) are a cornerstone of malaria prevention. Holes develop in LLINs over time and compromise their physical integrity, but how holes affect malaria transmission risk is not well known. Methods After a nationwide mass LLIN distribution in July 2012, a study was conducted to assess the relationship between LLIN damage and malaria. From March to September 2013, febrile children ages 6–59 months who consistently slept under LLINs (every night for 2 weeks before illness onset) were enrolled in a case–control study at Machinga District Hospital outpatient department. Cases were positive for Plasmodium falciparum asexual parasites by microscopy while controls were negative. Digital photographs of participants’ LLINs were analysed using an image-processing programme to measure holes. Total hole area was classified by quartiles and according to the World Health Organization’s proportionate hole index (pHI) cut-offs [< 79 cm2 (good), 80–789 cm2 (damaged), and > 790 cm2 (too torn)]. Number of holes by location and size, and total hole area, were compared between case and control LLINs using non-parametric analyses and logistic regression. Results Of 248 LLINs analysed, 97 (39%) were from cases. Overall, 86% of LLINs had at least one hole. The median number of holes of any size was 9 [interquartile range (IQR) 3, 22], and most holes were located in the lower halves of the nets [median 7 (IQR 2, 16)]. There were no differences in number or location of holes between LLINs used by cases and controls. The median total hole area was 10 cm2 (IQR 2, 125) for control LLINs and 8 cm2 (IQR 2, 47) for case LLINs (p = 0.10). Based on pHI, 109 (72%) control LLINs and 83 (86%) case LLINs were in “good” condition. Multivariable modeling showed no association between total hole area and malaria, controlling for child age, caregiver education, and iron versus thatched roof houses. Conclusions LLIN holes were not associated with increased odds of malaria in this study. However, most of the LLINs were in relatively good condition 1 year after distribution. Future studies should examine associations between LLIN holes and malaria risk with more damaged nets.